Perceptions of family physicians in Istanbul about e-cigarettes as smoking cessation aids: a qualitative study - Melis Selamoglu; Ayse Emel Onal; Bircan Erbas; Selma Karabey; Meryem Merve Oren; Mahmut Talha Ucar; Chris Barton (Addiction Science & Clinical Practice)
Abstract Background Family physicians (FPs) are the first point of contact for people who smoke who are seeking to quit smoking in Türkiye. We aimed to explore Turkish FPs knowledge, attitudes and perceptions of e-cigarettes as smoking cessation aids. Methods Eleven in-depth semi-structured interviews were conducted with FPs in Istanbul, Türkiye. Participants were recruited through purposeful sampling from respondents to a previous survey study completed with 243 participants in 2022. The survey explored the knowledge, attitudes and recommendations of FPs in Istanbul about e-cigarettes as smoking cessation aids. Participants indicated availability for a follow up qualitative interview. FPs were interviewed and audio files were transcribed verbatim. QSR NVivo was used to aid coding, thematic analysis and retrieval of quotes. Results FPs expressed they had little knowledge about e-cigarettes and this impacted their confidence to discuss these with their patients. They held a range of views on the harms of e-cigarettes and the potential for a gateway effect and dual use with tobacco cigarettes. FPs stated they would not recommend e-cigarettes as smoking cessation aids and half were not keen on a prescription model for e-cigarettes. FPs did not feel comfortable or have the confidence to answer patient questions about e-cigarettes if asked. They were keen to learn more about e-cigarettes and receive training and education to be able to better inform their patients about e-cigarettes as smoking cessation aids. Conclusion FPs in Türkiye require more understanding of e-cigarettes if they are to answer patient questions about using e-cigarettes to support smoking cessation. They perceived to be lack of evidence and research on the harms of vaping and as such were not currently willing to recommend them to patients. FPs desired more information and resources from trusted sources to support them to learn about e-cigarettes in order to discuss them with patients. Providing evidence-based information and upskilling FPs on e-cigarettes may increase their knowledge and confidence to have discussions about e-cigarettes for smoking cessation.